Pengendalian Hama Terpadu sebagai Instrumen Penguatan Agrikultur Berkelanjutan Perkebunan Jeruk di Desa Gadingkulon Kecamatan Dau Kabupaten Malang - Pramatya Sidqi Aulia Sarwanto; Andri Prasetyo; Muhammad Aryo Bahy Pramonoputra; Nadira Salim Badri; Claudia Endang Januwar; Nasywatha Shofi Pranata; Annisa Dian Pramesti; Amanda Dhea Margareta; Aliya Wahidatul Janah; Fabiola Gita Aslamy; Afif Imam Rahadi (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2025)
This research aims to study and offer solutions to the problem of fruit flies that attack citrus plantations in Gadingkulon Village through the Integrated Pest Control (PHT) approach. Fruit fly attacks have caused significant losses to citrus farmers, so an effective and sustainable control strategy is needed. PHT is implemented by integrating mechanical methods in the form of garden sanitation and yellow trap installation, as well as renewable technology approaches to suppress the population and life cycle of fruit flies. This activity is carried out through the stages of socialization, training, and group discussion forums (FGD) which involve the active participation of farmers as subjects as well as agents of change. This participatory approach aims to improve farmers' understanding and skills in implementing PHT techniques independently and consistently. The results of the activity showed that the combination of mechanical and educational methods was able to significantly reduce the intensity of fruit fly attacks. In addition, the benefits of this program can be reviewed from the economic aspect, in the form of increasing crop yields and farmers' income, as well as the ecological aspect, in the form of reducing the use of chemical pesticides that have a negative impact on the environment. Thus, the implementation of PHT in Gadingkulon Village shows great potential to be replicated in other areas that face similar problems, in order to support sustainable and environmentally friendly agricultural development.